STRATEGI PEMERINTAH KOTA BEKASI DALAM PENANGANAN KETERBATASAN LAHAN PEMAKAMAN DI TPU PERWIRA KOTA BEKASI - Nindya Ellise; Maulana Rifai; Prilla Marsingga (Jurnal Pemerintahan dan Politik, 2022)
The purpose of this study was to determine the government's strategy in handling the limited burial space at the TPU Perwira Bekasi City. This type of research uses descriptive qualitative research based on purposive sampling, the data collection techniques used are observation, interviews and documentation. Data analysis techniques are data reduction, data presentation, and drawing conclusions. The results of this study indicate that there are dimensions of programs, budgets and procedures (Wheleen Hunger, 2000) that have been running for more than 60% and are included in the "Good" category. In the program dimension, the Bekasi City government UPTD has made maximum efforts to realize a free funeral program. In the budget dimension, the Bekasi City Government allocates a budget of 10 billion for 2 ha without any intervention from the private sector. In the procedure dimension, the mechanism for making requests for funeral permits is running for up to 90% of those who have a burial land application permit (IPTM) in accordance with the Bekasi City Government Work Plan.Â Keywords : Government Strategy, limited spaces for graves, Bekasi City.